Department history research and collections in the service of understanding the Debrecen school of educational sciences - Brezsnyánszky, László; Rébay, Magdolna; Vincze, Tamás (Central European Journal of Educational Research, 2026)
Exploring the history of the Department of Educational Studies in Debrecen, as well as the history of university teacher training and the practice school, began in 2002 under the leadership of László Brezsnyánszky with the collaboration of the “Debrecen School” research group. In our study, we summarize the main results and present the collections under the supervision of the department, as well as the professional forums on departmental history organized by it. According to our findings, the Debrecen School of Educational Sciences – its various organizational units – possessed three functions: 1. It provided for the education of the scientific next generation in its own field of expertise; 2. It conducted training in its own discipline and announced lectures on pedagogical subjects for the interested circle of the student body; 3. It performed the instructional tasks of theoretical pedagogical courses for teacher candidates, and additionally carried out organizational and supervisory work in this field. The state university of Debrecen carried on the traditions of its predecessor, the Reformed College. In departments critical to the shaping of worldviews, such as pedagogy, Reformed faith and ecclesial commitment remained vibrant until 1950. In the years following the foundation (1912), lectures on educational science were held by the professor of the Department of Philosophy (Béla Tankó); later, the now independent Department of Pedagogy sought to strengthen its prestige with a more diverse and colorful range of lecture offerings. In his lectures, Professor Gyula Mitrovics strived to present the fields of science according to the traditional division of pedagogy (theory of education, history of education, didactics), while in his seminars, he covered the significance of the intelligence tests he conducted and of experimental pedagogy. Sándor Karácsony already spoke to his students about the practical questions of school educational work. The era of Béla Jausz and László Kelemen was about stabilization, the strengthening of the position within the Faculty of Arts, and the alignment with the direction and research designated by socialist educational science. During Kelemen’s leadership, the preparation for the independence of units growing out of the individual departmental groups took place.